Recurrent massive perivillous fibrin deposition treated with aspirin and enoxaparin: A case report - Baillie A. Bronner; Margaret Schermerhorn; Anna McCormick; Juliana Sung; Samantha de los Reyes (Elsevier, 2024)
Massive perivillous fibrin deposition (MPVFD) is a potentially devastating complication of pregnancy that occurs in 0.03-0.5% of deliveries and is associated with severe fetal growth restriction, stillbirth, and neurologic injury due to uteroplacental insufficiency. The management of patients with recurrent pregnancy loss secondary to MPVFD has not been widely studied. We describe the case of a healthy 19-year-old with a history of two prior intrauterine fetal demises at 35w6d and 36w6d secondary to MPVFD of the placenta who subsequently delivered a healthy infant at 33w6d after she had been treated in the prenatal period with aspirin and prophylactic enoxaparin. Antenatal treatment with daily aspirin and prophylactic enoxaparin as well as close antenatal follow-up may be an option for patients with recurrent pregnancy loss due to MPVFD.